2019
DOI: 10.3390/molecules24193583
|View full text |Cite
|
Sign up to set email alerts
|

Globular and Fibrous Proteins Modified with Deep Eutectic Solvents: Materials for Drug Delivery

Abstract: Proteinaceous materials have numerous structures, many of which aid in the roles they perform. Some need to impart strength while others need elasticity or toughness. This study is the first to investigate the modification of both globular and fibrous protein, namely, zein, soy protein and gelatin, using deep eutectic solvents (DES) to form bioplastics, which may have application in drug delivery systems. The effects of DES content on the thermal and mechanical properties of the material were determined. Zein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…6–9 They have also been explored for their key role in transdermal drug delivery, anticancer therapeutics and as cryoprotectants. 10–14 Apart from these applications, DESs are also known to provide an appropriate matrix for cell survival under extreme conditions such as the absence of water and critically low temperatures. 10 Thus these solvents in their pure and aqueous solutions provide attractive alternative media for various applications, such as protein crystallization and engineering, pharmaceutical design and cryobiology.…”
Section: Introductionmentioning
confidence: 99%
“…6–9 They have also been explored for their key role in transdermal drug delivery, anticancer therapeutics and as cryoprotectants. 10–14 Apart from these applications, DESs are also known to provide an appropriate matrix for cell survival under extreme conditions such as the absence of water and critically low temperatures. 10 Thus these solvents in their pure and aqueous solutions provide attractive alternative media for various applications, such as protein crystallization and engineering, pharmaceutical design and cryobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al have investigated the possibility of creating materials for drug delivery from proteins dissolved in deep eutectic solvents (Qu et al, 2019). They tested the plasticizing properties of deep eutectic solvents, in particular "Glyceline", choline chloride:glycerol 1:2, with two plant-derived globular proteins, zein from maize and soy protein.…”
Section: The Influence Of Choline-based Ionic Liquids On the Catalytic Activity Of Lipase Frommentioning
confidence: 99%
“…Furthermore, Fu et al have used a deep eutectic solvent as a medium for producing a molecularly imprinted polymer in order to extract β-lactoglobulin (Fu et al, 2019). Also in the section on the incorporation of high molecular weight compounds into deep eutectic solvents, it has been shown that nanofibers can be produced from lysozyme (Silva et al, 2018a(Silva et al, , 2018b and a pharmaceutically useful material can be created from gelatin in the "Glyceline" deep eutectic solvent (Qu et al, 2019).…”
Section: 7applications In Formulation For Drug Delivery and Biotechnologymentioning
confidence: 99%
“…Such links are needed to form biopolymer-IL supramolecular complexes in a more stable way than in the case of ionogels, or films, to deliver active compounds. 7,10…”
Section: Mechanical Properties and Release Abilities In Simulated Phymentioning
confidence: 99%
“…6 The release of API-IL from edible and resorbable matrices is the next step of using these drugs 7,8 , as in the case of protein-based materials because of numerous potential interactions between such hetero-polymers and active ingredient molecules 8,9 and recently highlighted especially for zein. 10,11 [Lidocainium][Ibuprofenate], named [Lid][Ibu], has a triple interest : (i) a plasticizing effect on biopolymers (e.g. PLA- [Lid][Ibu] 12 ) and two therapeutic roles due to its constitutive molecules 13 , with (ii) the cation (Lidocainium) as a local anaesthetic and (iii) the anion (Ibuprofenate) as nonsteroidal anti-inflammatory compound.…”
Section: Introductionmentioning
confidence: 99%